PUBLIC KNOWLEDGE, PRACTICES AND ATTITUDES TOWARDS COVID-19 IN AFGHANISTAN - Sayeed Naqibullah Orfan; Abdul Hamid Elmyar (Public Health of Indonesia)
Background: COVID-19 has tremendously affected the world including Afghanistan since its outbreak.